Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1152/jappl.1991.70.2.900
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal, electrolyte, and renal responses to exercise are intensity dependent

Abstract: Previous work indicates that the magnitude and direction of renal responses to exercise depend on the exercise intensity. To examine mechanisms responsible for these findings, renal and hormonal responses were studied in eight healthy male subjects (29.6 +/- 1.9 yr) before and immediately after four 20-min bouts of submaximal exercise (cycle ergometry) at work loads representing 25, 40, 60, and 80% of maximal oxygen consumption. Urine flow, osmotic clearance, glomerular filtration rate, and sodium excretion (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
4
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 0 publications
8
68
4
1
Order By: Relevance
“…They also reported that renal blood flow decreased by about 47% during exercise under these conditions. Declines in renal function during exercise are intensity-dependent (3,5,23,24) and generally in the range of 30%-60%. Our results collected on senior participants up to 80 years old extend these previous investigations obtained in young adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported that renal blood flow decreased by about 47% during exercise under these conditions. Declines in renal function during exercise are intensity-dependent (3,5,23,24) and generally in the range of 30%-60%. Our results collected on senior participants up to 80 years old extend these previous investigations obtained in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…In young adults, exercise depresses renal plasma flow and glomerular filtration rates [GFRs (3)(4)(5)], and induces excretion of plasma proteins in the urine (6). Postexercise proteinuria is more specifically related to the intensity than to the duration of the exercise (7).…”
mentioning
confidence: 99%
“…There are several potential pathways for stimulation of AVP release in exercising athletes. Controlled laboratory studies have demonstrated that as exercise intensity increases above 60% of maximal oxygen consumption, there are concomitant increases in AVP levels (61). Nonspecific stresses that are experienced by athletes and caused by factors such as pain, emotion, or physical exercise have been thought to cause nonosmotic release of AVP (62).…”
Section: Pathophysiologymentioning
confidence: 99%
“…All blood samples were analyzed for hematocrit (Hct), hemoglobin (Hb), total protein (TP), osmolality (P Osm), plasma concentrations of creatinine (P [AVP] was determined after extraction from plasma by the methods described by Freund and colleagues (13,14) on octadecylsilane cartridges (SEP-PAK C 18; Waters Associates). Extracted samples were assayed using a disequilibrium assay with the extracts incubated with the antiserum at 4°C for 72 h, followed by the addition of 125 I-labeled AVP (New England Nuclear, Boston, MA).…”
Section: Hypertonic Saline Infusion Protocolmentioning
confidence: 99%